Myofascial trigger points therapy increases neck mobility and reduces headache pain in migraine patients – pilot study - Maciej Olesiejuk; Małgorzata Chalimoniuk; Tomasz Sacewicz (BMC Musculoskeletal Disorders)
Abstract Background This study aimed to evaluate the effects of Ischemic Compression Myofascial Trigger Points (IC-MTrPs) therapy, applied mainly to the upper trapezius muscle (UTM), on: [1] cervical spine range of motion (CS-ROM), and [2] headache characteristics in migraine patients. Reduced CS-ROM can further contribute to musculoskeletal strain and neurological discomfort in migraine sufferers. The application of IC-MTrPs therapy is of particular interest because it targets these trigger points, potentially normalizing muscle tone and improving local blood flow, which may alleviate pain and restore mobility. Design A case series employing a repeated-measures design; pilot study. Methods Fifty-three adult female migraine patients were classified into three groups: episodic migraine without aura (MO, n = 31), episodic migraine with aura (MA, n = 15), and chronic migraine (CM, n = 7). Patients underwent seven sessions of IC-MTrPs therapy targeting the shoulder and neck muscles. Assessments were conducted across five sessions: pre-therapy (baseline), post-1st therapy, post-4th therapy, post-7th therapy, and at a 1-month follow-up. Outcome measures included: CS-ROM (assessed using an accelerometer system), subjective headache pain intensity (evaluated via the Visual Analog Scale (VAS)), and calcitonin gene-related peptide (CGRP) concentrations. Results CS-ROM for horizontal rotation and forward flexion improved significantly at the 1-month follow-up compared to pre-therapy (baseline) (P < 0.05). Headache intensity during a migraine attacks, as well as headache frequency and duration, significantly decreased at post-7th therapy compared to baseline across all patients (P < 0.05). The highest CGRP concentrations were recorded in CM patients (240.73 ± 79.51 ng/ml). While no significant changes in CGRP levels were observed in patients with MO, CGRP concentration in patients with MA increased significantly at the 1-month follow-up compared to baseline, rising from 151.70 ± 50.85 ng/ml to 176.17 ± 77.21 ng/ml. In patients with CM, the therapy did not result in statistically significant changes in CGRP levels, although reductions in headache frequency and intensity were noted. Conclusions IC-MTrPs therapy proved effective in increasing CS-ROM and alleviating headache characteristics in all migraine subtypes. However, no significant changes in CGRP levels were observed. Distinct characteristics and responses among different migraine subtypes highlight the need for tailored therapeutic approaches. Trial registration The study protocol was retrospectively registered on December 2, 2022, as a clinical trial in the international clinical trial database ClinicalTrials.gov (identifier: NCT05646160). Clinical trial number: not applicable.